A state-of-the-art review on uncertainty analysis of rotor systems. (15th January 2023) - Fu, Chao; Sinou, Jean-Jacques; Zhu, Weidong; Lu, Kuan; Yang, Yongfeng
Highlights: Uncertainty sources in rotor systems are identified and classified according to their nature. Principles and strengths and limitations of popular analysis methods are discussed. In-depth dynamic characteristics of rotor systems involving uncertainty are reviewed. Remaining challenges are summarized and future directions are pointed out. Abstract: Uncertainty handling and analysis of rotor systems have been active research areas during the last two decades. This paper provides a state-of-the-art review on the research progress of uncertainty treatment in rotor systems. Firstly, sources of uncertainties are identified and then classified according to their nature. Secondly, the most popular uncertainty analysis methods are summarized based on different types of uncertainties, including their basic principles, strengths and limitations. Thirdly, the dynamic characteristics of rotor systems under various uncertainties are described in detail, i.e., the natural characteristics and unbalanced responses, faulted rotor dynamics, stability problems and parameter identifications. Then, the reliability analysis, optimizations and vibration control for uncertain rotor systems are reviewed. Finally, comments on the latest research progress are made and outlooks on future research directions are highlighted. It is expected that this review will provide useful guidelines for designers and researchers towards the more efficient handling of uncertainty and robust dynamic analysis for rotor systems as well as insightful prospects, showing where extra efforts are needed.